Molecular biology of microbial ureases. - Mobley, H L (1995)
Urease (urea amidohydrolase; EC 3.5.1.5) catalyzes the hydrolysis of urea to yield ammonia and carbamate. The latter compound spontaneously decomposes to yield another molecule of ammonia and carbonic acid. The urease phenotype is widely distributed across the bacterial kingdom, and the gene clusters encoding this enzyme have been cloned from numerous bacterial species. The complete nucleotide sequence, ranging from 5.15 to 6.45 kb, has been determined for five species including Bacillus sp. strain TB-90, Klebsiella aerogenes, Proteus mirabilis, Helicobacter pylori, and Yersinia enterocolitica. Sequences for selected genes have been determined for at least 10 other bacterial species and the jack bean enzyme. Urease synthesis can be nitrogen regulated, urea inducible, or constitutive. The crystal structure of the K. aerogenes enzyme has been determined. When combined with chemical modification studies, biophysical and spectroscopic analyses, site-directed mutagenesis results, and kinetic inhibition experiments, the structure provides important insight into the mechanism of catalysis. Synthesis of active enzyme requires incorporation of both carbon dioxide and nickel ions into the protein. Accessory genes have been shown to be required for activation of urease apoprotein, and roles for the accessory proteins in metallocenter assembly have been proposed. Urease is central to the virulence of P. mirabilis and H. pylori. Urea hydrolysis by P. mirabilis in the urinary tract leads directly to urolithiasis (stone formation) and contributes to the development of acute pyelonephritis. The urease of H. pylori is necessary for colonization of the gastric mucosa in experimental animal models of gastritis and serves as the major antigen and diagnostic marker for gastritis and peptic ulcer disease in humans. In addition, the urease of Y. enterocolitica has been implicated as an arthritogenic factor in the development of infection-induced reactive arthritis. The significant progress in our understanding of the molecular biology of microbial ureases is reviewed.